AIRPORT GATE ASSIGNMENT FOR IMPROVING TERMINALS’ INTERNAL GATE EFFICIENCY - Lee, Jaehwan; Im, Hyeonu; Kim, Ki Hong; Xi, Sha; Lee, Chulung (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
This paper considers airport gate assignment (AGA) to evenly distribute passengers to airport internal gates (landside gate), where critical processes such as security check, immigration, and customs are performed. The paper focuses on AGA and the efficiency of landside gates. The AGA determines departure passengers’ entering gates and arrival passengers’ initial location in an airport. The initial location may settle passengers’ landside gate selection depending on their moving distances, which make congestion or idling on landside gate. To improve this inefficiency, we tried to adapt and modify AGA model by using quadratic mixed integer programming to assign gates with balanced passenger flow on each gate. We then performed a simulation experiment to verify the effect of proposed model on the internal gate efficiency. The result shows that the proposed model reduces the passenger processing time.